QUALITY MANAGEMENT OF ISLAMIC EDUCATIONAL INSTITUTIONS SERVICE (STUDY OF CUSTOMER SATISFACTION ANALYSIS IN MADRASAH IBTIDAIYAH AL-HUSNA CILEDUG TANGERANG CITY) - Mashud, Imam; Suradika, Agus; Ahmad, Gofur (International Journal of Educational Management and Innovation, 2021)
Management is a staple component that cannot separate from Islamic educational institutions. Without management, the purpose of the institution cannot realize optimally, effectively, and efficiently. Problems in educational institutions, usually dealing with the service to the customers of Islamic education. This research is qualitative research aimed to know about planning, organizing, implementing, and evaluating the quality management of Islamic education services. This research method uses a quantitative approach, in the process of data collection is carried out in four types of data collection techniques, namely observation, interview, documentation, and survey. The results of the calculation of customer satisfaction of Islamic education, in order to get a satisfaction index of 71% of the services provided by Madrasah Ibtidaiyah Al-Husna Ciledug, so that it must make improvements in the quality of service, this is because in the calculation of the overall Servqual gap value still shows a negative value of -0.71 to the service provided by Madrasah Ibtidaiyah Al-Husna Ciledug. Improvement of service quality carried out on attributes that have the highest gap. The purpose of improving the quality of service is to give parents satisfaction as customers of Islamic education can be accommodated.